The Effectiveness of a Training Program based on Erikson's Theory in Developing Independence Skills among Students with Learning Disabilities in Jordan - Khasawneh, Mohamad Ahmad Saleem (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2021)
This study aimed at identifying the effectiveness of a training program based on Erikson's theory in developing independence skills among students with learning disabilities in Jordan. The study population consisted of students with learning disabilities enrolled in resource rooms in public basic schools in Mafraq city for the academic year 2007/2008. The study sample consisted of sixty male and female students from the third, fourth, fifth, and sixth grades in the schools of Mafraq city, who were diagnosed by the resource room teacher as students with LDs. The sample was divided equally into two experimental and control groups. To achieve the objectives of the study, a collective training program was built, and the program included various activities and events carried out by the researcher and the resource room teacher in different ways and methods. The results of the study showed that there were statistically significant differences at (Î± < 0.05)) in the independence skills between the mean scores of the experimental and control groups on the post-test, and the difference was in favor of the experimental group. The results also showed no statistically significant differences at (Î± < 0.05)) in independence skills due to the interaction between gender and group variables on the post-test. There are statistically significant differences at (Î± < 0.05)) in the independence skills between the experimental and control group on the follow-up test, and the differences were in favor of the experimental group. The results were discussed in the light of the theoretical framework of the study and the results of previous studies and research in the field, then a set of educational recommendations and proposed studies were presented.AbstrakPenelitian ini mengidentifikasi efektivitas program pelatihan berdasarkan teori Erikson dalam mengembangkan keterampilan kemandirian di kalangan siswa dengan keterbatasan belajar di Yordania. Populasi terdiri dari siswa berkesulitan belajar yang terdaftar di sekolah dasar umum di kota Mafraq untuk tahun ajaran 2007/2008. Sampel terdiri dari enam puluh siswa laki-laki dan perempuan dari kelas tiga, empat, lima, dan enam yang didiagnosis oleh guru sebagai siswa dengan LDs. Sampel dibagi rata menjadi dua kelompok: eksperimen dan kontrol. Untuk mencapai tujuan penelitian, dibangun program pelatihan kolektif. Program tersebut mencakup berbagai kegiatan dan acara yang dilakukan oleh peneliti dan guru dengan cara dan metode yang berbeda. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan secara statistik pada (Î± < 0,05) dalam keterampilan kemandirian antara nilai rata-rata kelompok eksperimen dan kelompok kontrol pada post-test, dan perbedaan itu menguntungkan kelompok eksperimen. Hasil juga menunjukkan tidak ada perbedaan yang signifikan secara statistik pada (Î± <0,05) dalam keterampilan kemandirian karena interaksi antara variabel gender dan kelompok pada post-test. Ada perbedaan yang signifikan secara statistik pada (Î± <0,05) dalam keterampilan kemandirian antara kelompok eksperimen dan kelompok kontrol pada tes tindak lanjut, dan perbedaan itu mendukung kelompok eksperimen. Hasilnya dibahas dalam kerangka teoritis studi, hasil studi sebelumnya, dan penelitian di lapangan, kemudian serangkaian rekomendasi pendidikan dan studi yang diusulkan disajikan.